The effect of replacement of sea water with sea salt in the larval rearing of the freshwater prawn Macrobrachium rosenbergii (de man) - Ang, K.J. (Universiti Putra Malaysia, 2015)
A study was undertaken to determine the feasibility of replacing sea water with sea salt in the culture of the freshwater prawn larvae, Macrobrachium rosenbergii by using the "modified static water system". The larvae were cultured using five combinations of saltwater (Sa W) to sea water (Se W): 0% Sa W (control), 50% Sa W, 60% Sa W, 70% Sa W and 100% Sa W. Each treatment has 3 replicates at a density of 30 larvae/L. When 90% of the larvae metamorphosed to post larvae (PL), the experiment was terminated. Further observations were continued up to PL21 to determine their survival and growth rates under the different treatments. The survival rates of the larvae for treatments 0%, 50%, 60%, 70% and 100% Sa W were 78.61 +- 1.04%, 72.85 +- 1.81%, 49.54 +- 3.95%, 50.89 +- 3.03% and 0.0% respectively. There is no significant difference (p greater than 0.05) in survival rate, total length and wet weight between control and 50% Sa W but it was significant (p less than 0.05) between control and 60% and 70% Sa W. The survival rate of PL21 taken from 0%, 50%, 60% and 70% treatments were 90.42+-0.72%, 86.67+-1.74%, 83.42+-2.55% and 85.42+-2.49% respectively. There is no significant difference between the control and the 50% treatment (p greater than 0.05) in the survival rates, total length and wet weight but there is significant difference (p less than 0.05) between the control and the 60% and 70% Sa W. Based on this study, it may be concluded that up to 50% of sea water can be replaced by salt water in culturing the giant freshwater prawn larvae.